2017
DOI: 10.1002/ptr.5896
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of the Glycoprotein Isolated from the Chinese Yam (Dioscorea opposita Thunb)

Abstract: The yam (Dioscorea opposita Thunb) is a well-known edible food and widely used as the traditional Chinese medicine. The present investigation was designed to evaluate the immunomodulatory activity of glycoprotein (DOT) from yam and explore its possible molecular mechanisms. Results showed that the DOT could improve the cell immunity, humoral immunity and phagocytic system function of the normal mice. The DOT could also increase the production of TNF-α, interleukin-6 and nitric oxide and enhance the pinocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…There have been several reports about the anti‐inflammatory ability of polysaccharides, like Lentinula edodes and Ginkgo biloba . And strikingly, most researches proposed the essential role of the immune system in the anti‐inflammatory process including Dioscorea opposita . Severe inflammatory symptoms were below detection after CP treatment such as inflammatory cell infiltration, which indicated the possibility of its impact on the immune cells in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports about the anti‐inflammatory ability of polysaccharides, like Lentinula edodes and Ginkgo biloba . And strikingly, most researches proposed the essential role of the immune system in the anti‐inflammatory process including Dioscorea opposita . Severe inflammatory symptoms were below detection after CP treatment such as inflammatory cell infiltration, which indicated the possibility of its impact on the immune cells in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Niu and colleagues evaluated the effects of immune regulation of glycoprotein extracted from Rhizoma Dioscoreae in vivo and in vitro. It was shown that the glycoprotein significantly increased the serum level of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and nitric oxide (NO) and simultaneously promoted the pinocytosis activity of macrophages which are important in inherent immunity (Niu et al, 2017).…”
Section: Tcm Compounds and Their Preparations Based On Invigorating S...mentioning
confidence: 99%
“…For example, Niu and colleagues evaluated the effects of immune regulation of glycoprotein extracted from Rhizoma Dioscoreae in vivo and in vitro. It was shown that the glycoprotein significantly increased the serum level of tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), and nitric oxide (NO) and simultaneously promoted the pinocytosis activity of macrophages which are important in inherent immunity (Niu et al, 2017). Besides glycoprotein, peptides and polysaccharides extracted from Rhizoma Dioscoreae were also found to have strong abilities to modulate immune function by invigorating spleen, which was manifested by enhancing immune organs index, improving the pathology of the spleen, and increasing the level of immune active substances, including IL‐1α, IL‐6, interferone‐γ (IFN‐γ), immune globulin‐G (IgG), and IgM (Hao & Zhao, 2015).…”
Section: Tcm Compounds and Their Preparations For Oral Therapymentioning
confidence: 99%
“…(Chinese yam) is a common species and primarily contains 30 kD Class A dioscorin. 5 In recent years, researchers have reported that dioscorin derived from different species of yam displays similar biological activities (anticancer, antioxidant, carbonic anhydrase, trypsin inhibitor, and antiallergenic), 6−9 but their immunomodulatory activities differ. For example, dioscorins from Dioscorea alata stimulated the phagocytic activity of lymphoid cells more effectively than dioscorins from Dioscorea japonica, whereas D. japonica dioscorins enhanced the proliferation of lymphoid cells more effectively than D. alata dioscorins.…”
Section: Introductionmentioning
confidence: 99%
“…dioscorins improved macrophage phagocytic function, stimulated macrophage NO secretion, enhanced immunity, and stimulated proinflammatory cytokine expression in a mouse model. 5 In addition, D. opposita Thunb. increased the expressions of p38, JNK, ERK1/2, and nuclear factor κB (NF-κB) p65 proteins in RAW264.1 macrophages.…”
Section: Introductionmentioning
confidence: 99%